An on‐line school‐based substance use harm reduction programme: The Illicit Project randomized controlled trial results. - Debenham, Jennifer; Birrell, Louise; Champion, Katrina E.; Newton, Nicola (Addiction, 2024)
Aims: The aim of this study was to measure the effectiveness of an on‐line, neuroscience‐based harm reduction intervention (The Illicit Project) on substance use, harms and knowledge over a 12‐month period. Design: We used a two‐arm cluster‐randomized controlled trial. Setting: The study was conducted at eight secondary schools across New South Wales, Australia. Participants: A total of 950 (mean age = 15.9; standard deviation = 0.68) in grades 10–12 at participating schools in 2020 took part. Intervention and comparator: The Illicit Project intervention group (schools = five, n = 681) received an on‐line, universal substance use and harm reduction programme over three classes. The active control group (schools = three, n = 269) received school‐based health education as usual. Measurements Self‐report questionnaires assessed primary [alcohol, nicotine, cannabis, 3,4‐methylenedioxymethamphetamine (MDMA), cocaine and prescription drug misuse] and secondary outcomes (alcohol‐related harms and drug literacy) at baseline and the 6‐ and 12‐month follow‐up assessment. Findings Approximately 63% (n = 595) of the sample completed the 12‐month follow‐up assessment, including 58% of the intervention group (n = 396/679) and 66% of the active control group (n = 179/271). Participants in the intervention group had slower annual increases in binge drinking [odds ratio (OR) = 0.33, 95% confidence interval (CI) = 0.12–0.89], nicotine use (OR = 0.80, 95% CI = 0.52–1.23), MDMA use (OR = 0.14, 95% CI = 0.02–1.00), cocaine use (OR = 0.06, 95% CI = 0.01–0.64) and prescription drug misuse (OR = 0.07, 95% CI = 0.01–0.54) compared with the active control group. There was limited evidence of an intervention effect on cannabis use and alcohol‐related harm (P > 0.5). The secondary outcomes showed that the intervention group maintained higher levels of drug literacy knowledge (β = 3.71, 95% CI = 1.86–5.56) and harm reduction help‐seeking skills (β = 1.55, 95% CI = 0.62–2.48) compared with the active control group. Conclusion: The Illicit Project (an on‐line, neuroscience‐based substance use harm reduction intervention) was effective in slowing the uptake of risky substance use and improving drug literacy skills among late secondary school students in Australia, compared with school‐based health education as usual.